Protective Effect of Plumeria obtusa Leaves Extracts on Dexamethasone-induced Insulin-resistance Diabetes Mellitus in Rats - Gupta, Sumeet; Sharma, Hitendra; Morsy, Mohamed Aly; Nair, Anroop Balachandran; Kaur, Kamalpreet; Kumar, Satish; Dhanawat, Meenakshi (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Plumeria obtusa L., a potential medicinal plant, is still unexplored for its anti-diabetic effect. The objective of this study was to examine the protective effect of Plumeria obtusa leaves extracts on insulin-resistance diabetic rat model. Materials and Methods: Male Wistar rats were distributed into twelve groups. Dexamethasone was used to induce insulin-resistance diabetes mellitus. Three different doses of each extract (petroleum ether, ethanol and aqueous) were orally administered for 45 days. Biochemical estimations, as well as histological and scanning electron microscopy examinations, were done on the 45th day. Results: Statistically significant improvement in serum levels of glucose, glycosylated haemoglobin and insulin, as well as lipid profiles, were observed specifically with ethanol and aqueous extracts in comparison to the positive control group. Conclusion: The histological and scanning electronic microscopy studies revealed a significant improvement in various organs. Hence, this plant needs to be explored at the molecular level.
Keywords: Plumeria obtusa; Insulin-resistance diabetes mellitus; Lipid profile; Insulin; Scanning electron microscopy